Faktor-Faktor yang Mempengaruhi Produksi Biodiesel dari Minyak Sawit Mentah Menggunakan Katalis Padat Kalsium Karbonat yang Dipijarkan - Awaluddin, Amir; ', Saryono; Nelvia, Sri; ', Wahyuni (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2009)
The demand for petroleum has increased recently due to the increase of world population, industries andtransportation. Biodiesel (fatty acids methyl esters) has become attractive because of high price of petroleum,limited recourses of crude oil, and environmental concerns. Most biodiesel is produced by transesterification oftriglycerides of refined/edible type oils using methanol and homogeneous catalyst such NaOH and KOH. The useof heterogeneous calcined CaCO3 catalyst, has advantages such as the ease of phase separation betweencatalyst and biodiesel. This paper presents factors affecting the synthesis of biodiesel from crude palm using thecalcined CaCO3 catalyst . The synthesis is carried out by two steps, the acid-catalyzed pre-esterification of free-fatty acid and followed by base-catalyzed transesterification of triglycerides. A study of optimizing the reactioncondition of the esterification followed by transesterification of crude palm oil (CPO) is performed to obtainmaximum production of biodiesel. Under conditions of catalyst calcination temperature of 9000C, reactor time of1.5 hours, catalyst dosage of 1,5%, reaction temperature of 700C and methanol/oil molar ratio of 9 : 1, the oilconversion is 74,6%. The as-synthesized biodiesel meets the requirements of Indonesian National Standard (SNI)for biodiesel.